Promoting deep learning through online feedback in SPOCs - Filius, Renée Marianne; de Kleijn, Renske A.M.; Uijl, Sabine G.; Prins, Frans J.; Rijen, Harold V.M.; Grobbee, Diederick E. (Frontline Learning Research, 2018)
Higher education aims for deep learning and increasingly uses a specific form of online education: Small Private Online Courses (SPOCs). To overcome challenges that instructors face in order to promote deep learning through that format, the use of feedback may have significant potential. We interviewed eleven instructors and four students and organized a focus group to formulate scalable design propositions for instructors in SPOCs to promote deep learning. Propositions have been formulated according to the CIMO-logic. This study resulted in identification of four mechanisms by which the desired outcome (deep learning) can be achieved, which we describe here along with proposed interventions. Results show that the “online learning interaction model” can be deepened with these mechanisms: 1) Feeling personally committed, 2) Asking and providing relevant feedback, 3) Probing back and forth, and 4) Understanding one’s own learning process. To activate these mechanisms, scalable feedback interventions are described in three categories. Results at this relatively young field of SPOCs also show that feedback as a dialogical process may contribute to solving the current challenges of instructors in SPOCs to achieve deep learning with their students.